1996
DOI: 10.1210/en.137.12.5731
|View full text |Cite
|
Sign up to set email alerts
|

Activation of LH receptors expressed in GnRH neurons stimulates cyclic AMP production and inhibits pulsatile neuropeptide release

Abstract: The GT1-7 cell line of immortalized GnRH neurons has been shown to express receptors for GnRH, LH, and prolactin, as well as a variety of other hormones and transmitters. Treatment of GT1-7 cells with hCG caused a dose-dependent increase in cAMP production, with a rapid increase during the first 15 min and a subsequent decrease that was prevented by pre-treatment with pertussis toxin. Furthermore, the stimulatory effect of cholera toxin on cAMP production was inhibited by hCG in a dose-dependent manner. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Also, in hypothalamic neuronal GT1-7 cells, the elevation of intracellular cAMP levels by forskolin or application of 8-bromo-cAMP was found to mimic GnRH receptor activation by stimulating neurosecretion (24). Some recent reports have shown that GnRH can activate the G s -coupled adenylyl cyclase pathway.…”
mentioning
confidence: 85%
“…Also, in hypothalamic neuronal GT1-7 cells, the elevation of intracellular cAMP levels by forskolin or application of 8-bromo-cAMP was found to mimic GnRH receptor activation by stimulating neurosecretion (24). Some recent reports have shown that GnRH can activate the G s -coupled adenylyl cyclase pathway.…”
mentioning
confidence: 85%
“…An unexpected finding is that the medial pallium, a hippocampal homolog in anurans, does not express LHR, whereas the mammalian hippocampus shows the highest levels of expression of LHR (4). Although the functional significance of this species difference is not understood, expression of LHRs in hypothalamic areas, highly conserved among vertebrates, is likely to participate in the well established role of providing negative feedback to GnRH cell populations (10). Support for this hypothesis comes from the presence of GnRH-expressing cells in the POA and median eminence in the Xenopus brain, where LHRs are also expressed (40).…”
Section: Distribution and Functionality Of Lhrs In Comparison With Othermentioning
confidence: 99%
“…Based on these receptor distributions, several functions for LHRs have been hypothesized, including regulation of GnRH expressing cells (9)(10)(11), sensory information processing (12), modulation of hippocampal activity (8,13) and pathology (14), and neurosteroidogenesis (12). However, with the exception of the role of LHRs in regulating GnRH, direct in vivo tests for the function of gonadotropins within the CNS are few and include effects on the sleepwake cycle, activity, and stereotypic behavior in female rodents (15,16).…”
mentioning
confidence: 99%
“…In addition to regulating pituitary gonadotropin release, GnRH has extrapituitary actions in neural and nonneural tissues and in several types of tumor cells (1). Immortalized GnRH-producing neurons (GT1-7 neurons) express several G protein-coupled receptors (GPCRs), including those for GnRH and luteinizing hormone/ human chorionic gonadotropin (2,3), as well as ␣-and ␤-adrenergic (4), muscarinic (5), and serotonergic receptors (6). These cells retain many of the characteristics of the native GnRH neurons, including the ability to maintain pulsatile GnRH release (1,3).…”
mentioning
confidence: 99%